The Impacts of Political Risk to Financial Market Stability - Tang, Yip Ting Trevor (2018)
This paper aims to investigate the impacts of political risk to financial market stability in a broader approach. A greater variety of political risks are included such as legal system, violence, and terrorism. In addition, the different impacts between (1) Developed and Developing countries and (2) Democratic and Non-Democratic countries are assessed. The research is conducted in a quantitative approach by using a sample of 20 countries with 10 years of data. It considers distinct definitions of financial market stability by introducing comparable proxies.